SYNERGY Everolimus-Eluting Stent Noninferior to PROMUS Element Plus: Results from EVOLVE II Randomized Clinical Trial - Hoyle, Brian (MD Conference Express, 2014)
This article reports on the primary outcomes of the prospective, randomized, single-blind, multicenter EVOLVE II Clinical Trial to Assess the SYNERGY Stent System for the Treatment of Atherosclerotic Lesion(s) [EVOLVE II; NCT01665053], which assessed the safety and effectiveness of 2 different everolimus-eluting stents, the second-generation SYNERGY stent and the PROMUS Element Plus durable-polymer drug-eluting stent.